2016
DOI: 10.1002/1873-3468.12520
|View full text |Cite
|
Sign up to set email alerts
|

Divalent metal binding by histidine‐rich glycoprotein differentially regulates higher order oligomerisation and proteolytic processing

Abstract: The serum protein histidine-rich glycoprotein (HRG) has been implicated in tissue injury and tumour growth. Several HRG functions are regulated by the divalent metal Zn 2+ , including ligand binding and proteolytic processing that releases active HRG fragments. Although HRG can bind divalent metals other than Zn 2+ , the impact of these divalent metals on the biophysical properties of HRG remains poorly understood. We now show that HRG binds Zn 2+ , Ni 2+ , Cu 2+ and Co 2+ with micromolar affinities, but diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
(142 reference statements)
3
12
0
1
Order By: Relevance
“…The number of sites for Zn 2+ was consistent with Kassaar et al [47], although data by Priebatsch et al [48] demonstrated greater affinity for Zn 2+ (K d : 2.85). The discrepancy between the observed affinities was proposed by Priebatsch et al [48] to be potentially due to the non-favorable reaction conditions used in Kassaar et al [47].…”
Section: The Functional Significance Of Zn2+ Coordination Geometrysupporting
confidence: 86%
See 4 more Smart Citations
“…The number of sites for Zn 2+ was consistent with Kassaar et al [47], although data by Priebatsch et al [48] demonstrated greater affinity for Zn 2+ (K d : 2.85). The discrepancy between the observed affinities was proposed by Priebatsch et al [48] to be potentially due to the non-favorable reaction conditions used in Kassaar et al [47].…”
Section: The Functional Significance Of Zn2+ Coordination Geometrysupporting
confidence: 86%
“…The number of sites for Zn 2+ was consistent with Kassaar et al [47], although data by Priebatsch et al [48] demonstrated greater affinity for Zn 2+ (K d : 2.85). The discrepancy between the observed affinities was proposed by Priebatsch et al [48] to be potentially due to the non-favorable reaction conditions used in Kassaar et al [47]. The comparison between the orders of affinity for rbHRG (Cu 2+ : K d : 0.2 μM > Zn 2+ K d : 1 μM > Ni 2+ K d : 1.3 μM > Co 2+ : K d : 2.1 μM) by Morgan et al [36] and for HRG (Zn 2+ : Kd: 2.85 μM > Ni 2+ : K d : 3.35 μM > Cu 2+ : K d : 3.72 μM > Co 2+ : K d : 9.39 μM) by Priebatsch et al [48], demonstrates considerable differences.…”
Section: The Functional Significance Of Zn2+ Coordination Geometrysupporting
confidence: 86%
See 3 more Smart Citations